Service delivery and customers' satisfaction in some selected hotels in Ikeja areas of Lagos state / Tijani Nasiru ... [et al.] - Tijani, Nasiru; Okunola, G.A; Yina, Orga Donald (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The study evaluates the customer satisfaction in selected Hotels in Ikeja Area of Lagos. Table of random sampling technique was used to select 10 hotels from 27 hotels registered and recognized by Nigeria Tourism Development Corporation (NTDC) in the areas. A well structured questionnaire was used to collect necessary data. Findings revealed that the Hotels in the studies area were not giving their customers' satisfaction because what hotelier perceived as customers quality service differs from the guests' expectation. The study concluded that managers and proprietors of hotels should accord necessary recognition to professionalism and staff training to achieve customer satisfaction. The study is significant to manager of hotels, restaurants, hotel proprietors and human resources managers in meeting customer satisfaction especially in Lagos and in Nigeria in general.